2011
DOI: 10.1097/scs.0b013e3182077fbd
|View full text |Cite
|
Sign up to set email alerts
|

Role of RANK-RANKL-OPG Axis in Cranial Suture Homeostasis

Abstract: Craniosynostosis is a significant disorder affecting 1 in 2500 live births worldwide. Although a large body of work has focused on dural regulation and the contributions of molecular mediators such as fibroblast growth factor, bone morphogenetic protein, and transforming growth factor β, minimal attention has been directed toward osteoclast function in cranial suture biology. Receptor activator of nuclear factor κB (RANK) is an essential mediator of osteoclastogenesis and osteoclast activation. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Expression of Acp5 and Tnfrsf11a were significantly reduced in Bsp −/− vs. WT mouse calvaria at 14 dpn, with a similar trend at 26 dpn, and the same non-significant trend in Ctsk mRNA (Supplementary Figure 1C). Overall, involvement of craniosynostosis genes in the suture alterations in Bsp −/− mice could not be ruled in or out, however reductions in osteoclast markers suggests reduced osteoclast activity may contribute to decreased suture widths (Beederman et al, 2014; Lee et al, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Expression of Acp5 and Tnfrsf11a were significantly reduced in Bsp −/− vs. WT mouse calvaria at 14 dpn, with a similar trend at 26 dpn, and the same non-significant trend in Ctsk mRNA (Supplementary Figure 1C). Overall, involvement of craniosynostosis genes in the suture alterations in Bsp −/− mice could not be ruled in or out, however reductions in osteoclast markers suggests reduced osteoclast activity may contribute to decreased suture widths (Beederman et al, 2014; Lee et al, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Although they are important for normal maintenance of bone, the function of osteoclasts in cranial suture biology has not been thoroughly investigated. Lee and Spiguel et al found that if RANK expression is knocked down using si-RNA, bone density is increased in a murine, explanted cranial suture model (7). Thus, perturbation in the RANK-RANKL-OPG axis affects murine cranial suture fusion, implicating a role for osteoclasts in cranial suture biology.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoprotegrin (OPG) is a soluble inhibitor of RANK, and confers osteoclast apoptosis (5,6). Our laboratory has shown that suture fusion is correlated with a downregulation of RANK expression (7). This temporospatial relationship was shown in both murine and human suture samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). 32 Specifically, sentinel work characterized a temporospatial relationship between RANK protein expression and physiologic cranial suture closure in a murine model. Further delineation of osteoclastic modulators through proteomic and candidate gene approaches may spawn the development of animal models for the investigation of nonsyndromic craniosynostosis, as well as molecular-targeted therapies to treat the clinical disease.
Figure 3Model for RANK function in cranial suture biology.
…”
Section: Osteoclastic Related Pathwaysmentioning
confidence: 99%